COMPLICATIONS AFTER CARDIAC INJURIES - M. P. Korolyov; R. S. Sagatinov; Sh. K. Urakcheev; N. K. Pastukhova; Yu. A. Spesivtsev; E. S. Mezentseva (Вестник хирургии имени И.И. Грекова)
An analysis of 293 victims with cardiac and pericardium injuries was made. Cardiac complications could appear suddenly and be registered on any stage of treatment process. They differentiated by character and duration of wound process. Pericarditis took place in 288 patients. The syndrome of system inflammation reaction was noted in 47,9% of patients, a sepsis (sometimes severe sepsis) was in 14,3%. Complications in postoperative period were determined by posthypoxic and hemic hypoxia, coagulopathy. They were manifested by myocardial ischemia and thromboembolic complications. An acute myocardial infarction took place in 29 (9,8%) cases and rhythm and conductivity abnormalities were in 23 (7,8%) patients. The circulatory failure with clinical picture of pulmonary edema was developed in 12 (4,1%) cases. The lethality consisted of 44 (15%) patients.